Laporan Studi Kasus Penerapan Teknik Rileksasi Nafas Dalam Pada Pasien Post Op Sectio Caesarea (Sc) Dengan Masalah Nyeri Akut Di Ruang Bugenville Rumah Sakit Umum Daerah Tugurejo Semarang - Setyan Nur Safitri, Putri; Hastuti, Witri (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Sectio caesarea is one of the methods used in the health sector to assist in childbirth when unexpected problems occur during labour. One of the greatest fears of surgical patients is pain. Response Pain felt by patients is a side effect that arises after undergoing an operation. Pain caused by surgery is usually very painful for the patient. The purpose of this study was to provide an overview of the application of deep breathing relaxation techniques in postoperative Sectio Caesarea patients with acute pain problems. This research is a descriptive study in the form of a case review to explore the problem of nursing care by focusing on nursing care for Post Sectio Caesarea (SC) Patients with Acute Pain Problems in the Bugenville Room, Tugurejo Regional General Hospital, Semarang. The results of the study found that the mother experienced pain scale 6 which was felt when carrying out movement activities, experienced mobility restrictions with vital signs within normal limits. Actions taken by doing deep breathing relaxation technique therapy to overcome post section caesarea pain. After nursing care was carried out for three days, the subjective data of the mother was able to sit up without assistance.